Preparation, Structure, and Reactivity of Pseudocyclic β‐Trifluorosulfonyloxy Vinylbenziodoxolone Derivatives. Issue 13 (28th May 2021) - Yoshimura, Akira; Huss, Christopher D.; Liebl, Mackenzie; Rohde, Gregory T.; Larson, Scott M.; Frahm, Gunnar B.; Luedtke, Mattew W.; Schumacher, Tanner J.; Gardner, Zachary S.; Zhdankin, Viktor V.; Postnikov, Pavel S.; Yusubov, Mekhman S.; et al.
Abstract: Pseudocyclic β‐trifluorosulfonyloxy vinylbenziodoxolones were prepared starting from hydroxybenziodoxolones and alkynes in the presence of trifluoromethanesulfonic acid. The reaction of these compounds with azide anion leads to β‐azido vinylbenziodoxolones as products of vinylic nucleophilic substitution in which addition‐elimination reactions occur and the double bond configuration is retained. The structures of β‐trifluorosulfonyloxy vinylbenziodoxolone and β‐azido vinylbenziodoxolone were established by single crystal X‐ray diffraction. Abstract :